2020
DOI: 10.1001/jamanetworkopen.2020.7419
|View full text |Cite
|
Sign up to set email alerts
|

Association of Bariatric Surgery With Risk of Fracture in Patients With Severe Obesity

Abstract: IMPORTANCE Given the complex relationship between body mass index, body composition, and bone density and the correlative nature of the studies that have established the prevailing notion that higher body mass indices may be protective against osteopenia and osteoporosis and, therefore, fracture, the absolute risk of fracture in patients with severe obesity who undergo either Roux-en-Y gastric bypass (RYGB) or sleeve gastrectomy (SG) compared with those who do not undergo bariatric surgery is unknown. OBJECTIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 84 publications
0
32
0
1
Order By: Relevance
“…We examined a comprehensive set of bariatric surgeries that included Roux-en-Y gastric bypass, vertical sleeve gastrectomy, and gastric banding, and excluded procedure codes that indicated possible revision surgeries or treatment of complications from an earlier index bariatric surgery. 29 , 30 , 31 We excluded cases with evidence of possible surgical indications other than obesity, such as abdominal procedures for malignant neoplasms and abdominal ulcers. 29 To identify elective surgeries, we excluded patients admitted through the emergency department.…”
Section: Methodsmentioning
confidence: 99%
“…We examined a comprehensive set of bariatric surgeries that included Roux-en-Y gastric bypass, vertical sleeve gastrectomy, and gastric banding, and excluded procedure codes that indicated possible revision surgeries or treatment of complications from an earlier index bariatric surgery. 29 , 30 , 31 We excluded cases with evidence of possible surgical indications other than obesity, such as abdominal procedures for malignant neoplasms and abdominal ulcers. 29 To identify elective surgeries, we excluded patients admitted through the emergency department.…”
Section: Methodsmentioning
confidence: 99%
“…It is worth noting, however, that most patients included in these 3 studies underwent restrictive surgery. 15,19,25 Two more recent retrospective cohort studies 14,18 also did not find an increased risk of fractures after bariatric surgery compared with the population with obesity eligible for bariatric surgery. Furthermore, they suggested that surgery reduces the risk of fractures, especially in patients undergoing vertical gastrectomy.…”
Section: Global Fracture Riskmentioning
confidence: 95%
“…Among the included studies, 12 were observational studies (10 cohort studies, 1 case-control study, and 1 case series) 5,6,[13][14][15][16][17][18][19][20][21][22] and 3 interventional clinical studies (2 randomized and 1 nonrandomized). [23][24][25] Most of the studies were conducted in the United States, with the majority of participants being premenopausal women.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…135 Bariatric surgery appears to be a particularly strong risk factor for BMD loss 136,137 and fractures. [138][139][140] A 7-year prospective study after RYGB (baseline mean age 43 -8 years, BMI 42 -6 kg/m 2 ) found continuous decline in BMD and deterioration of bone microarchitecture, as well as reduced estimated bone strength compared with baseline and 2 years postsurgery. 137 A meta-analysis concluded that bariatric surgery significantly increases fracture risk.…”
Section: Effect Of Traditional Obesity Treatments and Bariatric Surgementioning
confidence: 99%